2008
DOI: 10.1002/adma.200702343
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency and Small Roll‐Off Electrophosphorescence from a New Iridium Complex with Well‐Matched Energy Levels

Abstract: It is well-known that, under electrical excitation, singlet and triplet excitons will be formed in organic light-emitting diodes (OLEDs) in the ratio of approximately 1 to 3 in the organic layers, where recombination of opposite charges occurs. The harvesting of triplet excitons for emission (termed as phosphorescence) cannot be obtained in common organic compounds because of the spin-forbidden rule. Thus, metal complexes, possessing the spin-orbit coupling effect caused by the heavy metal, are commonly used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 33 publications
4
53
0
Order By: Relevance
“…During the last decade, research on luminescent metal complexes has become important because of their possible application as dopant emitters in organic light emitting device technology [1][2][3][4][5][6]. In particular, interest in various gold(I) complexes has been stimulated by their tendency to give supramolecular structures such as pairs, rings, chains, and layers through closed shell d 10 aurophilic interactions and their resultant luminescent and anticancer properties [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, research on luminescent metal complexes has become important because of their possible application as dopant emitters in organic light emitting device technology [1][2][3][4][5][6]. In particular, interest in various gold(I) complexes has been stimulated by their tendency to give supramolecular structures such as pairs, rings, chains, and layers through closed shell d 10 aurophilic interactions and their resultant luminescent and anticancer properties [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal-based photoactive complexes have been extensively investigated in optoelectronics due to their high chemical stability and excellent luminescence properties [134]. Ruthenium-based complexes, tris(1,10-phenanthroline-4,7-diphenylsulfonate)ruthenium(II) (denoted as Ru(dpds) 3 ), have been studied by [76] assembly with LDH nanosheet to obtain orderly UTFs [83].…”
Section: Assembly Based On Anionic Metal Complexes and Small Moleculesmentioning
confidence: 99%
“…Mi et al reported efficient and thermally stable OLEDs using diphenylphthalazine iridium(III) [8]. Based on this work, it has been found that the ligands with an sp 2 -hybridized N atom adjacent to the chelating N atom, such as phenylpyridazine and phenylphthalazine derivatives [1], are beneficial for the iridium(III) complexes due to the shorter bond length and the stronger bonding strength between the chelating N atom and the Ir atom, compared with analogs which have a C atom instead of the non-chelating N atom. In one of our studies, cinnoline derivatives as another type of isomers of benzopyridazine besides phthalazine were now used to synthesize a novel cyclometalated Ir(III) complex, [(dpci-H) 2 Ir(dafo)](PF 6 ) (dpci-H = deprotonated 3,4-diphenylcinnoline, dpci; dafo = 4,5-diazafluoren-9-one).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclometalated Ir(III) complexes belong to the family of organometallic triplet emitters, which are of great interest because of their application in electroluminescent devices and sensors [1,2]. Owing to the strong spin-orbital mixing of heavy metal ions in phosphorescent complexes, both singlet and triplet excitons can be fully utilized, creating the possibility for electrophosphorescent dye-doped devices to reach an internal quantum efficiency of 100 % [3].…”
Section: Introductionmentioning
confidence: 99%